Feasibility of CT quantification of intratumoural 166Ho-microspheres - R. C. Bakker; R. Bastiaannet; S. A. van Nimwegen; A. D. Barten-van Rijbroek; R. J. J. Van Es; A. J. W. P. Rosenberg; H. W. A. M. de Jong; M. G. E. H. Lam; J. F. W. Nijsen (European Radiology Experimental, 2020)
Abstract Background Microspheres loaded with radioactive 166Ho (166Ho-MS) are novel particles for radioembolisation and intratumoural treatment. Because of the limited penetration of β radiation, quantitative imaging of microsphere distribution is crucial for optimal intratumoural treatment. Computed tomography (CT) may provide high-resolution and fast imaging of the distribution of these microspheres, with lower costs and widespread availability in comparison with current standard single-photon emission tomography (SPECT) and magnetic resonance imaging. This phantom study investigated the feasibility of CT quantification of 166Ho-MS. Methods CT quantification was performed on a phantom with various concentrations of HoCl and Ho-MS to investigate the CT sensitivity and calibrate the CT recovery. 166Ho-MS were injected into ex vivo tissues, in VX-2 cancer-bearing rabbits, and in patients with head-neck cancer, to demonstrate sensitivity and clinical visibility. The amount of Ho-MS was determined by CT scanning, using a density-based threshold method and compared with a validated 166Ho SPECT quantification method. Results In the phantom, a near perfect linearity (least squares R 2 > 0.99) between HU values and concentration of 166Ho was found. Ex vivo tissue experiments showed an excellent correlation (r = 0.99, p < 0.01) between the dose calibrator, SPECT, and CT imaging. CT recovery was on average 86.4% ex vivo, 76.0% in rabbits, and 99.1% in humans. Conclusion This study showed that CT-based quantification of Ho microspheres is feasible and is a high-resolution alternative to SPECT-based determination of their local distribution.